Characterization of a Novel Endophytic Actinomycete, Streptomyces physcomitrii sp. nov., and Its Biocontrol Potential Against Ralstonia solanacearum on Tomato - Xiaoxin Zhuang; Congting Gao; Chenghui Peng; Zhiyan Wang; Junwei Zhao; Yue Shen; Chongxi Liu (Microorganisms, 2020)
Bacterial wilt of tomato is a destructive disease caused by Ralstonia solanacearum throughout the world. An endophytic actinomycete with antagonistic activity, designated strain LD120T, was isolated from moss (Physcomitrium sphaericum (Ludw) Fuernr). The biocontrol test demonstrated that co-inoculation by the isolate and the pathogen gave the greatest biocontrol efficiency of 63.6%. Strain LD120T had morphological characteristics and chemotaxonomic properties identical to those of members of the genus Streptomyces. The diamino acid present in the cell wall was LL-diaminopimelic acid. Arabinose, glucose, rhamnose, and ribose occured in whole cell hydrolysates. The menaquinones detected were MK-9(H4), MK-9(H6), MK-9(H8), and MK-9(H2). The polar lipid profile was found to contain diphosphatidylglycerol, phosphatidylethanolamine, and phosphatidylinositol. The major cellular fatty acids were found to be iso-C16:0, iso-C17:0, anteiso-C15:0, and C16:1 ω7c. The DNA G+C content of the draft genome sequence, consisting of 7.6 Mbp, was 73.1%. Analysis of the 16S rRNA gene sequence showed that strain LD120T belongs to the genus Streptomyces, with the highest sequence similarity to Streptomyces azureus NRRL B-2655T (98.97%), but phylogenetically clustered with Streptomyces anandii NRRL B-3590T (98.62%). Multilocus sequence analysis based on five other house-keeping genes (atpD, gyrB, rpoB, recA, and trpB) and the low level of DNA–DNA relatedness, as well as phenotypic differences, allowed strain LD120T to be differentiated from its closely related strains. Therefore, the strain was concluded to represent a novel species of the genus Streptomyces, for which the name Streptomycesphyscomitrii sp. nov. was proposed. The type strain was LD120T (=CCTCC AA 2018049T = DSM 110638T).